The curse of Enola Gay - Abd Razak, Dzulkifli (1995)
"SHORTLY AFTER THE BOMB exploded in midair, sickness appeared, with prostration, high fever, vomiting and diarrhoea. Those who were directly hit died almost instantly, some charred beyond recognition. People were strewed all over the place, crying for help but in vain. Many more died before any meaningful help can be given." These were the words of Abdul Razak Abdul Hamid, the only Malaysian to experience and survive the Atomic Bomb attack in Hiroshima. It was on 6 August 1945 at precisely 8.15 am, when it happened, minutes after the B29 bomber Enola Gay flew over Hiroshima. The history of mankind was once again scarred by the horror of war. If the timehonoured code against the use of toxic chemicals was breached during the First World War, the second World War witnessed the violation of another timehonoured tradition. It marked the beginning of the nuclear era. For the first time, clouds of radioactive filth engulfed an entire city, razing it to the ground. Likened to a black rain, the effects of the firstever atomic bomb, innocently nicknamed The Little Boy, indiscriminately killed at least 100, 000 people and maimed and shocked thousands of other unsuspecting people of Hiroshima. Indeed the whole world reacted in disbelief.